2019
DOI: 10.1200/jco.2019.37.15_suppl.1506
|View full text |Cite
|
Sign up to set email alerts
|

Ten-fold increase in genetic testing in pancreatic and metastatic prostate cancer with implementation of point of care (POC) testing.

Abstract: 1506 Background: Germline genetic testing (GT) for cancer susceptibility is recommended for pancreatic and advanced prostate cancer patients, due to potential implications for targeted therapies and risk assessment of family members. Traditional cancer GT programs may create barriers for certain patient populations. To more effectively integrate testing into standard oncology care POC GT was introduced in early 2018 in a joint protocol with Memorial Sloan Kettering Cancer Center. Here we report pre and post P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Furthermore, a genetic counseling appointment was scheduled prior to germline testing, necessitating the capacity for increased GC availability which may not be replicable at other institutions. This latter hurdle has been previously addressed by Symecko and colleagues, who created a system of video-based pretest counseling and point-of-care PDAC genetic testing at the University of Pennsylvania in 2018 [22]. Although this system relied on provider referrals, streamlining of pretest procedures nevertheless increased the volume of germline testing by greater than sixfold.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a genetic counseling appointment was scheduled prior to germline testing, necessitating the capacity for increased GC availability which may not be replicable at other institutions. This latter hurdle has been previously addressed by Symecko and colleagues, who created a system of video-based pretest counseling and point-of-care PDAC genetic testing at the University of Pennsylvania in 2018 [22]. Although this system relied on provider referrals, streamlining of pretest procedures nevertheless increased the volume of germline testing by greater than sixfold.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the difference in test uptake did not appear to be explained by a difference in performance status or disease stage in the telehealth group and it is possible that logistics for international courier delivery was a barrier to testing for some patients. Point of care testing has demonstrated that the convenience of testing is a strong determinant of testing uptake in this population …”
Section: Discussionmentioning
confidence: 99%
“…There is recognition of 5-10% hereditary cancer risk associated with mPDAC diagnosis, which may be higher in certain subpopulations [ 83 , 84 , 85 ]. ASCO and NCCN guidelines recommend that germline testing be considered for all patients with mPDAC in recognition that up to half of the patients may not have a classical family history and germline BRCA mutations may carry treatment implications [ 86 , 87 , 88 , 89 ]. However, the implementation of testing across the population remains a significant barrier and is subject to ongoing research [ 89 ].…”
Section: Questionmentioning
confidence: 99%
“…ASCO and NCCN guidelines recommend that germline testing be considered for all patients with mPDAC in recognition that up to half of the patients may not have a classical family history and germline BRCA mutations may carry treatment implications [ 86 , 87 , 88 , 89 ]. However, the implementation of testing across the population remains a significant barrier and is subject to ongoing research [ 89 ]. After an initial response to platinum-based chemotherapy, the use of maintenance olaparib compared to placebo demonstrated improved PFS, suggesting activity with the parp inhibitor, but the lack of OS improvement and use of placebo as a control (as opposed to ongoing chemotherapy) casts doubt over its utility despite FDA approval [ 85 ].…”
Section: Questionmentioning
confidence: 99%